Stable polymer brushes with effectively varied grafting density synthesized from highly crosslinked random copolymer thin films. Issue 43 (3rd July 2018) - Kang, Hyungoo; An, Sol; Lee, Woo Jung; Kang, Ga Ryang; Kim, Sangwon; Hur, Su-Mi; Paeng, Keewook; Kim, Myungwoong
Abstract : Crosslinkable epoxy copolymers enable achieving highly stable P(S- b -MMA) brushes with controlled grafting density for close examination of phase separation behaviors. Abstract : We demonstrate the synthesis of poly(methyl methacrylate) (PMMA) and poly(styrene- b -methyl methacrylate) (P(S- b -MMA)) brushes on crosslinked random copolymer thin films, compositionally varied poly(styrene- r -glycidyl methacrylate) (P(S- r -GMA)), which can be further functionalized with a molecule featuring an initiator group upon crosslinking to form highly stable thin films. With careful optimizations, PMMA brushes were successfully grown from the surfaces of initiator functionalized P(S- r -GMA) via surface-initiated atom transfer radical polymerization. The grafting densities of the PMMA and P(S- b -MMA) brushes were effectively controlled to be in different density regimes by controlling the composition of P(S- r -GMA) and post-crosslinking functionalization methods. Synthesized BCP brushes were stable upon repetitive washing and thermal annealing processes even at high grafting density, highlighting that the outstanding stability of crosslinked P(S- r -GMA) thin films enables close examination of the morphology of thermally annealed P(S- b -MMA) brushes in different grafting density regimes.